2015
DOI: 10.1017/s0025315415001332
|View full text |Cite
|
Sign up to set email alerts
|

Form changes inAmiantis purpurata(Bivalvia, Veneridae) shells over the past 100,000 years in North Patagonia (Argentina)

Abstract: Amiantis purpurata shells from the San Matías Gulf (SMG) were analysed in order to compare both morphology and size throughout the late Quaternary in relation to environmental changes. Shells from modern beaches, Holocene marine assemblages (late Holocene, 3630 ± 100 years bp) and interglacial Pleistocene marine assemblages (MIS 5, 100 ka years bp) were studied by measuring the height and length, and using the elliptic Fourier analysis (EFA) to take an outline contour. The Pleistocene shells were smaller, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Gasparini et al (2016) reported a radiocarbon date from the beach-like deposit and, due to the sedimentary environment, considered it to be terrestrial limiting. An OSL date from the beach-like deposit gave a date of 60 ka (Beilinson et al, 2019), which also likely underestimates the true age. If this deposit formed during MIS 5, it gives a terrestrial-limiting elevation of 1.3 ± 3.1 m.…”
Section: Nicolás Vignogna III Quarrymentioning
confidence: 99%
See 3 more Smart Citations
“…Gasparini et al (2016) reported a radiocarbon date from the beach-like deposit and, due to the sedimentary environment, considered it to be terrestrial limiting. An OSL date from the beach-like deposit gave a date of 60 ka (Beilinson et al, 2019), which also likely underestimates the true age. If this deposit formed during MIS 5, it gives a terrestrial-limiting elevation of 1.3 ± 3.1 m.…”
Section: Nicolás Vignogna III Quarrymentioning
confidence: 99%
“…OSL ages were derived from quartz grains of samples collected at two sites in Uruguay (Rojas and Martínez, 2016) and three sites in Argentina (Martínez et al, 2016;Zárate et al, 2009;Beilinson et al, 2019). Analysis for the Uruguay samples and the site at Ezeiza, Argentina, was completed at the University of Illinois at Chicago (Rojas and Martínez, 2016;Martínez et al, 2016).…”
Section: Optically Stimulated Luminescence (Osl)mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifi cally, they objectively discriminate between close taxa and characterize intraspecific variation and its possible causes (e.g. Monferran et al 2013, Mazzini et al 2014, Aguirre et al 2015, Bayer et al 2016. Ostracods (Class Ostracoda), are small crustaceans with a low-magnesium calcite bivalve carapace ("hard parts") that totally encloses the body and appendages ("soft parts") (Meisch 2000).…”
Section: Introductionmentioning
confidence: 99%